Biocontrol agent Trichoderma harzianum strain FA 1132 as an enhancer of oil palm growth - Naher, Laila; Tan, Soon Guan; Yusuf, Umi Kalsom; Ho, Chai Ling; Abdullah, Faridah (Universiti Putra Malaysia Press, 2012)
Agricultural products are mostly and adversely affected by environmental pollution caused by chemicalresidues of pesticides which are used for plant disease management. Consequently, researchers look foralternative approaches of disease control such as biocontrol agents. The results of this study showed thatconidial suspension of the soil borne fungus Trichoderma harzianum strain FA 1132 can control Ganodermaboninense which causes basal stem rot (BSR) disease in oil palm. The conidial suspension treatment wasapplied by using Trichoderma-incorporated surface mulch. The disease severity index value (DSI) showedthat Ganoderma infected the root as early as at week 5, with a DSI value of 8.3%, while physical symptomsappeared in leaf at week 8. However, no disease symptom was observed in T. harzianum strain FA1132 treatedplants and it also markedly increased oil palm root and leaf weights.